Penerapan Model Pembelajaran Survey, Question, Read, Recite, Review (SQ3R) Untuk Meningkatkan Hasil Belajar Membaca Pemahaman Siswa Kelas IV - Abdul Halik; Nur Ilmi; Muh. Faisal; Nur Fadillah (Universitas Negeri Makassar, 2022)
This research is motivated by the low learning outcomes of students' reading comprehension. The purpose of this study was to determine the improvement of the learning process and learning outcomes for fifth grade students of UPTD SDN 47 Parepare City through the application of the Survey, Question, Read, Recite, Review (SQ3R) learning model. The approach used is a qualitative approach with the type of classroom action research (CAR). The subjects in this study were teachers and students of class V UPTD SDN 47 Parepare City in the 2021/2022 academic year. The data analysis technique used is qualitative data analysis techniques. Based on the results of the study, the data in the first cycle was in the sufficient category (C), while in the second cycle it was in the good category (B). The conclusion of this study is that the application of the Survey, Question, Read, Recite, Review (SQ3R) learning model can improve the process and results of learning to read and understand for fifth grade students UPTD SDN 47 Parepare City.